Relevance of a subjective quality of life questionnaire for long-term homeless persons with schizophrenia. Issue 1 (December 2017) - Girard, V.; Tinland, A.; Bonin, J.; Olive, F.; Poule, J.; Lancon, C.; Apostolidis, T.; Rowe, M.; Greacen, T.; Simeoni, M.
Abstract Background Increasing numbers of programs are addressing the specific needs of homeless people with schizophrenia in terms of access to housing, healthcare, basic human rights and other domains. Although quality of life scales are being used to evaluate such programs, few instruments have been validated for people with schizophrenia and none for people with schizophrenia who experience major social problems such as homelessness. The aim of the present study was to validate the French version of the S-QoL a self-administered, subjective quality of life questionnaire specific to schizophrenia for people with schizophrenia who are homeless. Methods In a two-step process, the S-QoL was first administered to two independent convenience samples of long-term homeless people with schizophrenia in Marseille, France. The objective of the first step was to analyse the psychometric properties of the S-QoL. The objective of the second step was to examine, through qualitative interviews with members of the population in question, the relevance and acceptability of the principle quality of life indicators used in the S-QoL instrument. Results Although the psychometric characteristics of the S-QoL were found to be globally satisfactory, from the point of view of the people being interviewed, acceptability was poor. Respondents frequently interrupted participation complaining that questionnaire items did not take into account the specific context of life on the streets. Conclusions Less intrusive questions, more readily understandable vocabulary and greater relevance to subjects' living conditions are needed to improve the S-QoL questionnaire for this population. A modular questionnaire with context specific sections or specific quality of life instruments for socially excluded populations may well be the way forward.